Video transcoding technique using tree–based multi–level block partitioning in OFDM network. (18th April 2014) - Awaghad, Shakti; Pokle, Sanjay B.
Performing an efficient transcoding of large sizes of video in highly unpredictable and dynamic wireless network like orthogonal frequency–division multiplexing (OFDM) is a major challenge in the area of video transcoding. Such issues can be addressed if an efficient transcoder is designed that has smart access to multiple coding parameters and statistics of input video file. Therefore, the proposed system introduces a transcoding technique that considers performing large size video file in OFDM. The accomplishment of this technique is done using multi–level frame block partitioning, a tree–based approach that assist to have better formulation of non–rigid and complex mobility for evaluating non–translational mobility between blocks. Massively large size blocks are considered using standard dataset to perform an efficient transcoding. The results are evaluated for peak signal–to–noise ratio (PSNR) and bit rate for visualising the perceptual quality of the transcoded frames along with simultaneous comparison with frequently used prior work considering H.264 and Affine–16 standards.